ANALISIS FAKTOR PENINGKATAN MINAT BELI PRODUK UMKM DI KOTA TASIKMALAYA - suci putri lestari; Kusuma Agdh R (Jurnal Manajemen, 2020)
The purpose of this study is to determine factors that can increase product buying interest. Factors analyzed include UMKM product quality factors and service quality factors and see which factors are most influential. This research was conducted in the city of Tasikmalaya with UMKM subjects engaged in work including geulis, paying geulis and batik, the study population was all Tasikmalaya residents using probability sampling methods by distributing questionnaires to 120 consumers who had used / bought UMKM products. in the city of Tasikmalaya. The analytical tool used is the Regression genre. From these studies it can be seen that the factors that can increase buying interest of UMKM products in the city of Tasikmalaya are product quality factors with a significance level of 0.012 below 0.05 and significance for service quality factors equal to 0.00 below 0.05 with a level of influence of 31% can increase interest in buying UMKM products in the city of Tasikmalaya.